Genetic and Molecular Relationships Between Chronic Obstructive Pulmonary Disease and Abdominal Aortic Aneurysm: Insights from a Multi-Omics Approach - Jian Wang; Yuemeng Li; Yun Li; Jamol Uzokov; Zhaoxuan Zhang; Xiaoxu Zhang; Deying Jiang; Han Jiang; Azad Hussain; Chen Chen; Jian Zhang; Yanshuo Han (Cardiovascular Innovations and Applications)
Chronic obstructive pulmonary disease (COPD) and abdominal aortic aneurysm (AAA) are both severe conditions with complex etiologies and substantial comorbidities. Previous studies have suggested a potential relationship between these diseases, but the underlying genetic and molecular mechanisms remain unclear. We used bidirectional two-sample Mendelian randomization (MR) to investigate the causal relationship between COPD and AAA. Expression quantitative trait loci (eQTL) analysis was performed with GTEx V8 summary statistics for aortic and lung tissues. Single-cell sequencing data from GEO datasets were analyzed to identify differentially expressed genes. Finally, a phenome-wide association study (PheWAS) was conducted to explore the broader implications of identified pathogenic genes. We identified a genetic correlation between COPD and AAA. MR analysis revealed that COPD had a significant causal relationship with AAA (P < 0.05). SMR analysis identified 48 common genes associated with both COPD and AAA. Single-cell sequencing identified key genes, thus suggesting their potential roles as pathogenic factors. PheWAS further supported the pleiotropy and broader effects of these genes on various phenotypes. Our findings demonstrated a significant causal relationship between COPD and AAA. An integrative multi-omics approach provided a comprehensive understanding of the molecular mechanisms underlying these diseases.